Milky Way globular clusters on cosmological timescales - II. Interaction with the Galactic centre - Ishchenko, Marina; Sobolenko, Margaryta; Kuvatova, Dana; Panamarev, Taras; Berczik, Peter (Astronomy and astrophysics, 2023)
Aims: We estimate the dynamical evolution of the interaction of globular clusters’ with the Galactic centre that dynamically changed in the past. Methods: We simulated the orbits of 147 globular clusters over a 10 Gyr lookback time using the parallel N-body code ‘φ-GPU’. For each globular cluster, we generated 1000 sets of initial data with random proper motions and radial velocities based on the observed values. To distinguish globular clusters interacting with the Galactic centre, we used the criterion of a relative distance of less than 100 pc. We used four external potentials from the IllustrisTNG-100 database, which were selected for their similarity to the present-day Milky Way, to simulate the structure of the Galaxy at different times. Results: We obtained approximately three to four globular cluster interactions per billion years at distances of less than 50 pc and approximately five to six interactions per billion years at distances of less than 80 pc among the studied 147 globular clusters that had close passages near the Galactic centre. We selected ten of them for detailed study and found almost 100% probability of an interaction with the Galactic centre for six of them. Conclusions: According to our results, the maximum interaction frequency of globular clusters with the Galactic centre in the Milky Way is likely to be a few dozens of passages per billion years within a central zone of 100 pc. This low frequency may not be sufficient to fully explain the relatively high mass (of order 107 M⊙) of the nuclear star cluster in the Milky Way if we consider only the periodic capture of stars from globular clusters during close encounters. Therefore, we must also consider the possibility that some early globular clusters were completely tidally disrupted during interactions with the forming nuclear star cluster and the Galactic centre.
Veröffentlicht online: 02. Juni 2023
Gesehen am 14.08.2023